2009
DOI: 10.1007/bf03405548
|View full text |Cite
|
Sign up to set email alerts
|

Heat Awareness and Response among Montreal Residents with Chronic Cardiac and Pulmonary Disease

Abstract: ustained heat waves have struck both North America and Europe in the recent past. Impacts on human health have been dramatic: in August 2003, an estimated 1,067 Parisians died prematurely during the course of 9 uncharacteristically hot days; 1 an estimated 739 Chicago residents died as a consequence of a 7-day heat wave in 1995. 2 The ill and elderly are among those most vulnerable to the ravages of extreme heat. 3 On very hot days, older individuals 4 and persons with cardiac insufficiency, obstructive pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…A qualitative study by Wolf et al (2010aWolf et al ( , 2010b interviewing persons aged over 75 in the United Kingdom (UK) learns that participants did not consider themselves as old, or threatened by heat while they identify others of the same age group as vulnerable (Wolf et al, 2010a). Interestingly, in a study on heat perception in people with chronic cardiac and pulmonary disease most of the chronically ill population did perceive themselves to be susceptible to heat and reported implementing preventive actions in response (Kosatsky et al, 2009).…”
Section: Effectiveness In Alerting Human Responsementioning
confidence: 99%
“…A qualitative study by Wolf et al (2010aWolf et al ( , 2010b interviewing persons aged over 75 in the United Kingdom (UK) learns that participants did not consider themselves as old, or threatened by heat while they identify others of the same age group as vulnerable (Wolf et al, 2010a). Interestingly, in a study on heat perception in people with chronic cardiac and pulmonary disease most of the chronically ill population did perceive themselves to be susceptible to heat and reported implementing preventive actions in response (Kosatsky et al, 2009).…”
Section: Effectiveness In Alerting Human Responsementioning
confidence: 99%
“…[36] Most respondents in Canadian studies did perceive heat as a personal risk and also reported that they would take actions to stay cool during extreme heat. [40, 98] Finally, the perceived risk of heat was not predictive of air conditioning use among residents with poor cardio-respiratory health in Montreal[37] suggesting that low perceived risk is not always a barrier to staying cool.…”
Section: Proximal Mechanisms Of Heat Exposure and Susceptibilitymentioning
confidence: 99%
“…Researchers have investigated how and why the public and, more specifically, vulnerable populations, participate in heat preparedness (Abrahamsom et al, 2008;Kosatsky et al, 2009;Richard et al, 2011;Semenza et al, 2008;Sheridan, 2007). Related studies generally measure the frequency or likelihood of behaviors in heat events.…”
Section: Introductionmentioning
confidence: 99%